Event Management and Image Building: Analyzing Affective, Cognitive, and Overall Images in Indonesia’s Cultural Industry - Rudi Prasetyo Ardi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
The culture produced in the cultural industry has shifted from merely possessing artistic value to prioritizing economic value. One strategic element that can be utilized to support the development of the cultural industry is the organization of events. Event management plays a strategic role in the cultural industry, ensuring the successful transformation of cultural ideas into real experiences that have economic value while strengthening social meaning. Cultural events often serve as platforms to showcase local cultural heritage, traditions, and creativity to a wider audience, both domestically and internationally. This study examines the influence of the event on enhancing perceptions of the cultural sector using a quantitative methodology. The sample used in this study was 70 respondents. Data collection was carried out by asking respondents to complete a questionnaire relating to their experience attending the cultural event and their assessment of the image as a cultural tourism destination. SPSS was used to examine the information collected from the questionnaire. The results show that the Event variable has a significant influence on the Cognitive Image (CK), Affective Image (CA), and Overall Image (CO) of the destination. The t-test shows that the relationship between Event and the three image dimensions has a p-value <0.05, which indicates a strong and significant influence. Events designed with informative, emotional, and interactive aspects in mind will significantly contribute to the formation of the overall image. In a practical context, the implication is that event organizers need to ensure the quality of the holistic experience to continuously strengthen the overall image.